Voltage Flicker Real-time Detection Based on Recursive Degree Method - Tiejun Cao (Institute of Advanced Engineering and Science, 2015)
Traditional flicker detection methods accurately extract the amplitude envelope as the premise, the complexity of large amount of computation. This paper presents a new real-time detection of voltage flicker method, analysis method with recursive frequency carrier signal frequency; use of the adjacent three-point sampling data, the frequency carrier signal frequency, sampling frequency voltage flicker waveform obtained by the current envelope size. Of harmonic pollution by noise or flicker between the signals, the low-pass filtering results are not affected. Simulation results show that: The method to directly detect flicker signal, the process is simple, computational load and real time, tracking performance, with a certain anti-noise and inter-harmonic interference suppression capability, suitable for real-time detection of voltage flicker. DOI: http://dx.doi.org/10.11591/telkomnika.v13i1.6826